Fruit peel waste: A sustainable food source for fish culture - Aditi Thakur; Amit Kotiyal; Joshi Thoudam (World Development Sustainability, 2025)
Fruit peels that are usually discarded as agricultural residues serve as a rich source of various nutrients, such as carbohydrates, proteins, vitamins, and minerals, necessary for the growth and development of any fish. Moreover, their low cost and available nutritional composition provide a solution for resource limitations and waste disposal issues, and they can also be used as a cheap and green substitute for conventional fish diets. Several researchers have pointed out that fruit peel waste is an acceptable culture feed resource for aquatic animals, especially tilapia catfish and carp fish. This improves the growth performance of the fish, feed utilization efficiency, and their well-being in general. Furthermore, utilizing fruit peel waste is also favorable in meeting sustainable development goals by improving food security, environmental protection, and resource efficiency in aquafeed production. Advances in technology are also necessary if the solution is to be widely accepted. This includes nutritional diversity, processing methods, politics, and public opinion. More research is needed, as well as studies to optimize processing methods for assessment of nutritional value and acceptance of fruit peel waste in aquafeed formulations for the development of the aquaculture sector without putting a toll on the environment.